Flexural Behavior of One-Way Slabs Reinforced with Welded Wire Mesh under Vertical Loads - El-Sayed S. Ewida; Rasha T. S. Mabrouk; Nasser El-Shafey; Akram M. Torkey (Salehan Institute of Higher Education, 2022)
This paper aims to study the behavior of one-way concrete solid slabs reinforced with welded wire mesh to investigate the efficiency of using welded wire mesh in the construction of structural slabs as a replacement for ordinary steel bars. This research included experimental and analytical programs. Nine 700×1050 mm one-way simple specimens and six 525×1050 mm continuous one-way slabs with two equal spans were tested under point, line, and uniform static loads. The experimental program studied the use of welded mesh and the number of layers utilized. Numerical analysis was conducted using finite element modeling developed using the ABAQUS 6.13 software package. Experimental and analytical results showed good correlation: the number of layers of welded metal mesh and load type significantly affected the peak vertical load capacity of simple and continuous slabs, with slabs showing higher values with welded mesh than those of ordinary reinforcing bars. In addition, using welded metal mesh to reinforce solid slabs enhanced their cracking behavior as well as their ductility. Doi: 10.28991/CEJ-2022-08-04-03 Full Text: PDF